Review on Microalgae Cultivation Using Wastewater for Biofuel Production: A review - ธรรมเสน่ห์ เสาวภัคย์; เกาศล รศ.ดร.ธนิยา (Srinakharinwirot University Engineering Journal, 2020)
The integrations of wastewater treatment and microalgae-based biofuel have attended considerable. This paper describes the overview of microalgae in terms of biofuel productivity, cultivation of microalgae, harvesting microalgae and method for converting microalgae biomass to biofuel productions. The species of microalgae mostly used for cultivating in the wastewater to produce biofuel are presented. There are two major systems for cultivating microalgae: 1) opened system (raceway, circular and unmixed pond) and 2) closed system (photobioreactor, tubular and flat plate). The suitable selection of harvesting method is very critical because it can reduce the overall cost. Microalgae can be harvested by flocculation, flotation, filtration and gravity, and centrifugal sedimentation. In the present paper, the energy conversion process is explained and can be classified into thermochemical and biochemical conversions. Microalgae biomass can be used in a wide range of applications, including fertilizers, nutraceuticals, cosmetics, wastewater treatment, fish and animal feeds, and biofuels. Furthermore, microalgae biomass can also be converted into bio-oil, ethanol, methane, biodiesel and syngas. The selection of the conversion process depends on the species of microalgae, the final productivity and the possible economic factor. Most researchers are investigated the sustainable energy source as an alternative to fossil fuels. The microalgae are identified as the best feedstock to be convert into a biofuel production. The microalgae cultivation does not need a large land, possesses a high growth rate, and enhances the amount of lipid for a biofuel production. There have been few studies involving microalgae biofuel production using industrial wastewater. Finally, the future directions for integrated wastewater treatment and microalgae biofuel production are suggested.